Study of Dissipative Losses in AC-Biased Mo/Au Bilayer Transition-Edge Sensors - Sakai, K.; Adams, J. S.; Bandler, S. R.; Chervenak, J. A.; Datesman, A. M.; Eckart, M. E.; Finkbeiner, F. M.; Kelley, R. L.; Kilbourne, C. A.; Miniussi, A. R.; Porter, F. S.; Sadleir, J. S.; et al. (Journal of low temperature physics, 2018)
We are developing kilo-pixel arrays of transition-edge sensors (TESs) for the X-ray Integral Field Unit on ESA's (European Space Agency's) Athena observatory. Previous measurements of AC-biased Mo/Au TESs have highlighted a frequency-dependent loss mechanism that results in broader transitions and worse spectral performance compared to the same devices measured under DC (Direct Current) bias. In order to better understand the nature of this loss, we are now studying TES pixels in different geometric configurations. We present measurements on devices of different sizes and with different metal features used for noise mitigation and X-ray absorption. Our results show how the loss mechanism is strongly dependent upon the amount of metal in close proximity to the sensor and can be attributed to induced eddy current coupling to these features. We present a finite element model that successfully reproduces the magnitude and geometry dependence of the losses. Using this model, we present mitigation strategies that should reduce the losses to an acceptable level.